2022
DOI: 10.3390/ijerph191610238
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of Pb and Other Associated Elements in Soil Dust 15 Years after the Introduction of Unleaded Fuel and the Human Health Implications in Pretoria, South Africa

Abstract: Leaded fuel has been reported to contain certain amounts of toxic trace metals such as Pb and Cadmium (Cd), which may have negative impacts on humans and the environment. Unleaded fuel was introduced to South Africa in 2006 with the aim of reducing and eventually eliminating the negative impact of leaded fuel on the environment. However, trace metals are usually nonbiodegradable, and it may therefore be necessary to monitor their presence in the environment so as to evaluate their possible impact on human heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…So far, the soil pollution status has been assessed based on the concentration of each contaminant parameter [10], [11], as well as for soil quality parameters. In real conditions, various contaminant parameters and soil quality are incalculable, especially with regard to organic contaminants [12], [13], so the assessment takes a long time and is expensive.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the soil pollution status has been assessed based on the concentration of each contaminant parameter [10], [11], as well as for soil quality parameters. In real conditions, various contaminant parameters and soil quality are incalculable, especially with regard to organic contaminants [12], [13], so the assessment takes a long time and is expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Lead (Pb) has been added to gasoline since the 1920s to improve combustion engine performance. The use of leaded gasoline was officially banned in South Africa in 2006 (1).…”
Section: Introductionmentioning
confidence: 99%
“…Reports have shown that vehicular emissions increase the concentration of heavy metals such as lead (Pb), arsenic (As), cadmium (Cd) and chromium (Cr) in soil and in the environment, and this has been attributed to petrol use in most cases (1). On the average between 1990 and 2013, a total of 250,000 deaths in Africa were linked to vehicular emissions (6) evoking the need for regulations.…”
Section: Introductionmentioning
confidence: 99%
“…This is a significant gap in the research, as petrol stations are known to be a potential source of pollution due to the handling and storage of petroleum products. The lack of research on this topic raises concerns about the possible impact of toxic elements on the environment, the health of petrol station workers and customers, as well as the equipment used to deliver fuel (Olowoyo et al 2022). A possible scenario is the release of toxic elements into the environment through accidental spills or leaks from storage tanks or pipelines.…”
Section: Introductionmentioning
confidence: 99%